COMPARATIVE MORPHOLOGICAL TYPOLOGY OF ENGLISH AND RUSSIAN (Web of Teachers: Inderscience Research, 2025)
This article thoroughly examines the morphological features of English and Russian by providing extensive comparisons of their inflectional and derivational processes. It highlights essential differences in noun declension, verb conjugation, adjective agreement, numeral usage, possessive and definiteness marking, as well as morphological irregularities and patterns of word formation. Through numerous illustrative examples, the article demonstrates typological contrasts between the analytic structure of English and the fusional system of Russian. The findings offer valuable insights for linguistic theory and practical pedagogical applications in language teaching, translation studies, and contrastive linguistics.